CEO Expectations in terms of PR roles - Benita Steyn (Communicare)
The aim of this empirical study was to determine the chief executive’s role expectations of the most senior manager or practitioner responsible for the corporate communication (public relations) function in the organisation, in terms of the PR strategist (a strategic role at top management level), the PR manager and the PR technician. A conceptualisation of the role of PR strategist preceded the empirical study, differentiating it from the historical roles of PR manager and PR technician. The most important finding was that CEOs in the sample empirically verified the conceptualised role of the PR strategist. In view of the findings of the Excellence Study that shared expectations between top management and the corporate communication manager should exist for an organisation to achieve excellent communication (Dozier, Grunig & Grunig 1995), this study made an important contribution by establishing a benchmark regarding CEO expectations of the most senior manager responsible for the corporate communication function